Problems of Mechanized Tunneling In Gassy Ground Conditions a Case Study: Nousoud Water Transmission Tunnel - Tali, Naser; Lashkaripour, Gholam Reza; Ghafoori, Mohamad; Hafezimoghadas, Naser (International Journal of Geography and Geology, 2014)
Current advances in science, followed by development of excavation equipments technology resulted in growth of tunnelling projects for different purposes. In spite of conducting exploratory studies prior to these projects, in some cases due to of impassable paths, the studies are limited to certain areas. Hence, during geotechnical studies, it is possible that all problems facing tunnelling not be detected. Therefore, lack of awareness of these conditions can result in a lack of proper planning and consequently lead to problems during the projects. Due to the lack of knowledge and consequently not predicting and planning the projects, drilling of the second sector of Nousoud water transmission tunnel, -26 km long- has been faced with many problems including emission of hydrogen sulfide and methane gas and drainage of high volumes of water containing dissolved gas into the tunnel, which has led to the loss of life, loss of working efficiency, as well as increased project costs. In this study, problems occurred in this project, reasons behind them will be addressed; and the solutions to these problems will be mentioned. The results of the study have shown that oil-bearing formations of the region and the immigration of gases coming from these formations have let the gas entered into the tunnel. In addition, due to the high solubility of hydrogen sulfide and methane gas in water on one hand, and hydrated formations with high permeability on the other hand, caused the influx of large quantities of water and therefore the concentration of these gases in the tunnel.